(untitled) (Journal of Nobel Medical College, 2013)
Hypertension is one of the major risk factor for an increased risk of stroke, myocardial infarction, end-stage renal disease, congestive heart failure and peripheral vascular disease. The kidney is a main target of organ damage in hypertension. Microalbuminuria is one of the earliest indications of kidney injury in patients with hypertension. Total of 50 cases and 50 controls are enrolled into the study. Their blood pressure was measured and spot urine sample was analyzed for Microalbumin. Blood pressure and Microalbumin were statically elevated in case group in comparison to control group. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 9-12 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7665